Students’ Perceptions Towards the Use of Podcasts in EFL Classroom: A Case Study at a University of Uzbekistan - Sotlikova, Rimajon; Haerazi, Haerazi (Universitas Pendidikan Mandalika, 2023)
Integration of Information and Communication Technology (ICT) has emerged as a significant factor in the realm of language education, yielding notable impacts. To shed light on this phenomenon, a case study was conducted to delve into the perceptions of students and attitudes of teachers regarding the utilization of podcasts in the teaching-learning process. The research problem addressed in this study aimed to explore students' perceptions toward the incorporation of podcasts in the English as a Foreign Language (EFL) classroom, as well as their understanding of the limitations and impact of podcasts on their language skill development. The study recruited 40 students and 2 teachers from the National University of Uzbekistan as participants. Data collection involved the distribution of questionnaires to students and conducting interviews with teachers. The questionnaires comprised 17 statements to gauge the participants' viewpoints. The findings revealed that a majority of respondents expressed their fondness for podcasts (80.2%), strongly agreeing that the use of podcasts is enjoyable (69.9%). Moreover, the researcher observed positive attitudes from both students and teachers toward the integration of podcasts in the EFL classroom. Students believed that podcasts had the potential to enhance their listening and speaking skills. Teachers, on the other hand, perceived podcasts as an effective tool for fostering students' collaborative and cooperative work skills, as well as their creative thinking strategies. However, challenges associated with the effective utilization of podcasts in the classroom also surfaced, prompting further exploration into optimal implementation strategies.